Pengaruh Gaya Hidup Hedonisme, Desain Produk, Citra Merk, dan Persepsi Harga Terhadap Keputusan Pembelian Smartphone Merk Apple - Yoland Shinta Nara; Mulkan Ritonga; Siti Lam`Ah Nasution (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to examine the influence of hedonistic lifestyle, product design, brand image, and price perception on purchasing decisions for Apple smartphones. The research employed a quantitative method with data processing using the SPSS 23 application. The findings indicate that, partially, hedonistic lifestyle, brand image, and price perception have a positive and significant influence on purchasing decisions, while product design does shows a negative and significant effect. Simultaneously, hedonistic lifestyle, product design, brand image, and price perception together influence the purchasing decisions of Apple smartphones. These findings suggest that lifestyle factors, brand perception, and price perception play a more dominant role in influencing consumers' interest in purchasing Apple products compared to the aspect of product design.